PERAN LEGALITAS USAHA DAN DIGITAL MARKETING SEBAGAI STRATEGI DALAM MENINGKATKAN OMSET PENJUALAN UMKM (STUDI KASUS PADA UMKM DI WILAYAH KELURAHAN BONGKARAN) - Rahmawati, Maretta Ayu; Witjaksono, Gideon Budi (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
Establishing a business is important to have a strong legal basis in order to get legal protection from the government, both for large-scale businesses and micro-scale businesses such as MSMEs. With clear business legality, it will have its own impact on MSMEs such as business continuity, the level of public trust to buy these products, and has an indirect impact on the turnover obtained. MSME players must be able to keep up with the times and choose one of the media to be used as a promotional tool for their business. This is because social media is one of the promotional tools that can be used to reach a wider range of consumers at a low cost. The research method used this time is a descriptive qualitative research method using MSME actors in the Bongkaran Village area as sources. The results of interviews represented by 3 MSMEs found several similarities in mindsets regarding the role of business legality and digital marketing for the businesses they run. The results obtained from this study show that MSMEs consider that the existence of business legality and digital marketing will have an impact on increasing sales turnover.